Design and development of a web-based teacher payroll system at Al-Hikmah Middle School Medan - Pamugi, Rizki; Br Saragih, Nidia Enjelita (Institute of Computer Science (IOCS), 2023)
The Online Payroll Application for Al Hikmah Middle School in Medan is an innovative solution for efficiently and transparently managing the payroll process within the school environment. This application is specifically designed to meet the financial administration needs of the school, including calculating employee salaries, tax deductions, and maintaining a salary history record. The system leverages cutting-edge technology to ensure data accuracy and security. With the implementation of this application, it is expected to increase efficiency in payroll management, reduce potential human errors, and provide greater transparency in school financial administration.